Biosafety / Biotechnology: about this dossier - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
It is widely accepted that investments in science, technology and innovation are essential for economic development. The rapid changes that are taking place due to advances in biotechnology and information and communication technologies (ICTs) support thi